Synergistic Ethnopedagogy for Energy Conservation: Cultivating Character and Culture through Cempluk Dance in Elementary School - Nabilla Fissalma; Siti Faizah; Riska Pristiani (Actual Insight, 2026)
The erosion of local culture in the digital age challenges character education in elementary schools. Research on traditional dance rooted in energy conservation philosophy, such as the Cempluk Dance, remains scarce. This explanatory case study analyzes the internalization of character values through Cempluk Dance ethnopedagogy at Kalisongo Elementary School 3, involving two key informants (a classroom teacher and a dance instructor). Data were collected through observation, interviews, and documentation. The findings reveal that the Cempluk Dance program, as a mandatory extracurricular activity, successfully integrates local wisdom into the Merdeka Curriculum. Internalized character values include self-confidence, cultural pride, energy conservation, and good manners. A key success factor is the strong synergy between the school and the community, which reflects social capital as a theoretical framework. The novelty lies in the energy-saving philosophy derived from the local history of “Kampung Cempluk” and the engagement of students' cognitive, affective, and psychomotor domains. This study proposes a Synergistic Ethnopedagogy model comprising three pillars: character value internalization rooted in local history, school–community synergy as social capital, and structured curriculum support. This model offers a replicable framework for integrating local wisdom into character education within the Merdeka Curriculum.